Предмет: Математика,
автор: vika5487
3-(4х-1)=2х-3(х-3)
помогите пожалуйста,а то у меня ща мозг треснет
Ответы
Автор ответа:
0
Ответ: 3-4x+1=2x-3x+9
-4x-2x+3x=-3-1+9
-3x=5
X=-0, 6
Пошаговое объяснение:
margo1302:
5 разделить на -3 = -5/3
Автор ответа:
1
Ответ:
- 1 2/3
Пошаговое объяснение:
3-(4х-1)=2х-3(х-3)
3-4х+1=2х-3х+9
-4х-2х+3х=9-3-1
-3х=5
х=5÷(-3)
х=-5/3=-1 2/3
Похожие вопросы
Предмет: Литература,
автор: raite363
Предмет: Литература,
автор: dwerit
Предмет: Физика,
автор: ereminae88p6kfmo
Предмет: Биология,
автор: kkyrzova
Предмет: Математика,
автор: 1yes